E-GOVERNANCE AND SERVICE DELIVERY IN NIGERIA: CHALLENGES AND PROSPECTS - Ihemadu, Michael Chinazam; Anyiam, Chidi Gandhilawson (African Journal of Social and Behavioural Sciences, 2024)
The study aimed at examining the problems and prospects of adopting governance to achieve effective and efficient service delivery in Nigeria. To achieve the objective of the study, the researcher made use of content analytical technique whereby the study heavily relied on secondary data obtained from articles published in reputable journals, official publications, relevant books, etc. At the end of the analysis, the paper found that challenges of inadequate infrastructure, cybersecurity risks, and digital literacy gaps underscore the need for strategic interventions to overcome barriers to the effective implementation of e-governance initiatives. On the other hand, the study discovered that governance holds a lot of prospects for the country such as providing information job vacancies, an e-policing system, a medium for information dissemination, and economic development among others. The paper therefore recommends, among others, that Nigeria should take advantage of the opportunities presented by digital technologies to address her service delivery challenges and guarantee the welfare of the citizens, the government should provide ICT infrastructure, there should be an enactment of ICT laws in the country, the government should show commitment to making e-governance achieve successes in the country, etc. The study concludes that e-governance is the sine qua non for the actualization of simple, moral, accountable, responsive and transparent administration in the country.